Analisis Kendala Program Peremajaan Sawit Rakyat (PSR) terhadap Potensi Pertumbuhan Ekonomi Petani Sawit Rakyat. - Syafira, Retno; Nasution, Zulkifli; Charloq, Charloq (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to analyze the effect of the community oil palm replanting program on the economic growth of community oil palm farmers in Batu Bara Regency. This research uses quantitative methods with multiple linear regression analysis techniques. Primary data was obtained from 75 respondents of smallholder oil palm farmers in Batu Bara District. The results showed that administration and human resources have a positive and significant influence on the economic growth of smallholders. Meanwhile, oil palm land, facilities and infrastructure, and sustainability have no influence on the economic growth of smallholders. This study implies that it is important to increase training and technical support for assistants and smallholders. The government needs to provide financing and incentives to encourage farmers' participation in the smallholder oil palm replanting program. A holistic economic growth strategy is needed, such as diversification of oil palm products, improvement of the value chain, and integration with other sectors. It is necessary to build strong cooperation with relevant stakeholders to improve program implementation and maximize economic benefits for smallholders.